2018
DOI: 10.21577/0100-4042.20170188
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Based Nanocomposite Hydrogels With Zeolite: Evaluation of the Sorption Process of Pesticide Paraquat

Abstract: PARAQUAT. In this work, nanocomposites formed from the natural polymer carboxymethylcellulose in combination with the polyacrylamide polymer and zeolite were obtained and characterized in relation to pesticide sorption capability. Hydrogels are three-dimensional network with large capacity of water or biological fluid adsorption. They have biocompatibility, biodegradability and non-toxicity properties, ensuring this class of polymers is widely used in different agriculture fields. Thus, the objective of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Additionally, the presence of -OH groups in the chemical structure of both alginate and starch polysaccharides also favored the pesticide adsorption, as well as the hydrophobic interactions. 20,21 The sp 2 hybridization of the pyridinic ring becomes the structure with weakly polar characteristics whereas this hybridized form is more electronegative than sp 3 hybridization, also present in the pesticide structure. This factor also improved paraquat absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the presence of -OH groups in the chemical structure of both alginate and starch polysaccharides also favored the pesticide adsorption, as well as the hydrophobic interactions. 20,21 The sp 2 hybridization of the pyridinic ring becomes the structure with weakly polar characteristics whereas this hybridized form is more electronegative than sp 3 hybridization, also present in the pesticide structure. This factor also improved paraquat absorption.…”
Section: Resultsmentioning
confidence: 99%
“…For zeolite-hydrogel nanocomposites, an important fact to be highlighted is that paraquat molecules may not have diffused between the channels of the zeolite structure because their molecules have dimensions of approximately 15 Å and the zeolite pores channels have sizes around 4 Å. 21,25 It is not observed a very significant effect on the adsorption capacity of nanocomposite hydrogels caused by crosslinker type. This no variation is possibly being masked by the addition of nanostructures, showing a competitive interaction sites, i.e., polymeric chains-paraquat and zeolite/nanoclay-paraquat.…”
Section: Adsorption Behavior Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…Besides slow-release fertilizers, Cataldo et al (2021) explained that zeolites can be also applied in agriculture as carriers of herbicides, fungicides and pesticides (Barbosa et al, 2018), soil conditioners (Yasuda et al, 1998), heavy metals sequestration (Kumar et al, 2007), water adsorption (Xiubin & Zhanbin, 2001), reducing of undesirable odours caused by H 2 S and NH 3 emission in animal husbandry (Kithome et al, 1999), antifungal activity (Rumbos et al, 2016), photosynthesis enhancement by the adsorption of carbon dioxide molecules and their gradual release (Montanari & Busca, 2008), heat stress (Ainsworth & Rogers, 2007), aquaculture (Asgharimoghadam et al, 2012) and animal feed additive (Shurson et al, 1984).…”
Section: Zeolites In Agriculture Applicationsmentioning
confidence: 99%
“…Also, it was found that the main zeolite applied as a slow‐release fertilizer so far is clinoptilolite, which is a natural zeolite, whereas the main industrial residue used for the synthesis of zeolites is fly ash from coal. It is believed that applied research related to the synthesis of zeolites and their application in agriculture will continuously grow in the future because of their high efficiency as slow‐release fertilizer, and according to Xie and Su (2020), because zeolites have unique properties, and can also be used in other emerging applications, such as: carriers of herbicides, fungicides and pesticides (Barbosa et al., 2018), water treatment, atmospheric purification, agriculture and industrial catalysis (Cao et al., 2023).…”
Section: Summary Of Scientometric Analysismentioning
confidence: 99%
“…O que tem justificado a aplicabilidade de hidrogéis principalmente na área farmacêutica [23][24][25] e na agricultura para liberação controlada de nutrientes e pesticidas. [26][27][28] Especificamente na área agrícola, os hidrogéis vem sendo utilizados devido a sua biodegradabilidade, síntese de baixo custo e alta reprodutibilidade. O objetivo do trabalho foi compreender a influência de soluções salinas e pH na capacidade de absorção de água de bionanocompósitos constituídos de CMC/PAAm/nanoargila laponita RDS.…”
Section: Introductionunclassified